2018
DOI: 10.1002/app.46110
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a pilot scale module of thin film composite hollow fiber membrane for osmotic pressure‐driven processes

Abstract: Polyamide thin film composite hollow fiber membranes have advantages in their unique structure compared to flat sheet membranes. This study examined interfacial polymerization methods for fabricating pilot scale hollow fiber membranes (membrane area: 1.2 m2, number of hollow fiber strands: 1200). For use in osmotic pressure‐driven processes, a one‐pot hydrophilic interfacial polymerization procedure was developed simultaneously to modify the surface property and synthesize polyamide thin film. With the procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…For instance, lab-scale investigations of Shon et al [32] revealed that using a configuration where the DS was facing the active layer (pressure retarded osmosis (PRO) mode) reduced membrane rejection for boron in comparison to the system with the DS facing the support layer (FO mode). The effect of these configurations (PRO and FO mode) were also found to be critical by Park et al [7], as ECP becomes a key factor of membrane performance. Park et al [7] minimized the negative effects of ECP by developing an HFFO membrane with a novel interfacial polymerization (IP) process and by changing the module configuration.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…For instance, lab-scale investigations of Shon et al [32] revealed that using a configuration where the DS was facing the active layer (pressure retarded osmosis (PRO) mode) reduced membrane rejection for boron in comparison to the system with the DS facing the support layer (FO mode). The effect of these configurations (PRO and FO mode) were also found to be critical by Park et al [7], as ECP becomes a key factor of membrane performance. Park et al [7] minimized the negative effects of ECP by developing an HFFO membrane with a novel interfacial polymerization (IP) process and by changing the module configuration.…”
Section: Introductionmentioning
confidence: 92%
“…The effect of these configurations (PRO and FO mode) were also found to be critical by Park et al [7], as ECP becomes a key factor of membrane performance. Park et al [7] minimized the negative effects of ECP by developing an HFFO membrane with a novel interfacial polymerization (IP) process and by changing the module configuration. The temperature is another extensively studied parameter [24,25,33,34,35,36] that affects membrane rejection and water flux.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…As a pressure‐driven separation process, membrane‐based seawater desalination module is a crucial device of industrial processes . Yet, it suffers from the issue of energy consumption (represents >50–60% of total costs), since the separation performance cannot be significantly increased and even a small increase in separation efficiency results in great energy losses .…”
Section: Introductionmentioning
confidence: 99%